Power, Knowledge, and Marginalization: A Foucauldian Analysis of Children from Low-Income Immigrant Households in Norway - Agyare, Patrick (Research in Social Sciences and Technology- OpenED Network, 2025)
This study critically analyzes the discursive constructions of immigrant children from low-income households in Norwegian official publications between 2014 and 2024. The study uses Foucauldian discourse analysis to explore the representation of these children, the power dynamics and knowledge claims present in these discourses, and the implications for policy interventions and resource allocation. The analysis focuses on publications from key institutions, including the Directorate of Integration and Diversity, the Ministry of Children and Families, the Ministry of Labor and Social Inclusion, the Norwegian Labor and Welfare Administration, and Statistics Norway. The findings reveal that the portrayal of these children as vulnerable and socio-economically disadvantaged frequently exacerbates their challenges due to their immigrant background and poverty status. While such narratives drive targeted interventions aimed at alleviating poverty, they risk reinforcing hierarchical power dynamics and perpetuating the marginalization of immigrant families by focusing on remedial measures rather than addressing systemic inequalities. The study identifies a deficit-based framing that emphasizes dependency and vulnerability, which overlooks the potential, resilience, and agency of immigrant children. Instead, it advocates for a shift towards policies that address structural inequalities, promote social inclusion, and emphasize empowerment. A more comprehensive, intersectional approach to policy is recommended—one that not only provides economic support but also ensures equitable access to education, housing, and employment opportunities while dismantling systemic barriers. The findings underscore the necessity for transformative policies that challenge existing power structures and prioritize social justice, equity, and inclusive communities that better align with the host society’s values and social structure.